Articulações em conjunto: o financiamento da transição rumo ao desenvolvimento sustentável - Lima, Roberta Amado de (2014)
Nowadays it is evident the need for structural changes from an awareness related to the current way of the so-called business as usual , which is destroying the conditions for life on Earth. Thus, the objective of this work is to present a reflection on the ways to finance the transition towards a sustainable development from a critical point-of-view linked to power relations. This study was developed based on a literature review and an analysis of recent publications considering the topicality of the subject. In Chapter 1 we introduced the historical context in which the idea of sustainable development emerged, as well as some of its conceptual aspects related to the economic development theory. In Chapter 2 we discussed the targeting of resources to facilitate the sustainable development, which requires a less unequal society and the maintenance of an ecosystem balance. In this chapter we also discussed about international cooperation, private investments and social cooperation, as well as the deviations of resources to tax havens. Finally, the last chapter is about governance at a national and international level. In addressing this issue we pointed out the need for a more democratic governance structure, which promotes the articulation of the interests of civil society in decision making, also assuring a more equitable allocation of public resources. We highlighted the importance of orientation and measurement of policy performance based on new indicators that reflect the economic, social and environmental dimensions of reality. Indeed sustainable development depends on global agreements. However, considering the complexity of reaching a consensus among different nations, the preservation of the conditions of human life on Earth will depend much more on the performance of democratic nations, representing the interests of their citizens both in a national and in an international level